Multiscale multifeature vision learning for scalable and efficient wastewater treatment plant detection using Hi-Res satellite imagery and OSM - Randhawa, Sukanya; Randhawa, Guntaj; Sivak, Olena; Zech, Johannes; Martin, Maria; Zipf, Alexander; Li, Yuze (Proceedings of the 1st ACM SIGSPATIAL International Workshop on Advances in Urban-AI, 2025)
Filling data gaps in various global regions requires a robust approach that can accurately provide detection results from earth observation data. One of the challenges arises from significant heterogeneity in satellite images and variation in features and characteristics for specific ground objects like Wastewater Treatment Plants (WTPs). To overcome these challenges, we propose a novel multiscale multifeature hybrid model. This model leverages the power of deep learning-based object detection models, namely Yolov6, RTMDET, EfficientDET, and Domain Adaptation, to accurately and efficiently identify WTP locations worldwide. Our approach focuses on performance enhancements, including reduced false positives (FPs) and broad coverage. The strategies for achieving these improvements involve effective data processing approaches, model tuning, and adaptation. Moreover, we optimize training data features using Volunteered Geographic Information (VGI) data. We demonstrated the effectiveness of the suggested approach for three diverse global regions: Germany, France, and Malaysia. Our study gives new insights into WTP distribution when compared to existing databases like OpenStreetMap (OSM). The resulting pipeline delivers good results even in challenging rural and urban context. Moreover, it is well-suited for generating large scale WTP datasets, which is useful for many applications such as Critical Water Infrastructure mapping, Urban Planning, Climate Action and many more.